Paleolimnology of Lake Manitoba: the Lithostratigraphic Evidence - Last, William; Teller, James (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 2002)
AbstractLake Manitoba, the largest lake in the prairie region of North America, is one of the most intensively studied lacustrine basins in western Canada. New AMS 14C dating, together with mineralogical, geochemical, and lithostratigraphic analyses of the 14-m-thick, offshore sediment sequence, document a complex Holocene history in which water levels and limnological conditions were controlled by the interplay of changing climate, variable river and groundwater inflow, and differential isostatic rebound. Varves, ice-rafted debris, and clast-rich laminated sediment record deposition in the lake when the basin was part of proglacial Lake Agassiz. As Agassiz retreated northward, Lake Manitoba became isolated by about 8500 14C yrs BP, and for the next 800 years was characterized by mainly shallow water to dry conditions. Deeper and more stable water conditions returned to the Lake Manitoba basin by 7700 14C yrs BP probably due to the damming effect of differential isostatic rebound and decreasing aridity. For the next 3000 years, relatively stable lake levels and water compositions were maintained, reflecting a delicate balance between differential isostatic rebound, climate, inflow of the Assiniboine River, and groundwater contribution. At ~4500 14C yrs BP the Assiniboine River was rerouted to its present easterly path, by-passing Lake Manitoba, and resulting in loss of a significant component of the lake’s hydrologic budget. Water levels dropped and the offshore sediments were once again subaerially exposed. By 3700 14C yrs BP, a cooler and wetter climate, together with continued southward transgression of water, compensated for the loss of fluvial input, resulting in reflooding of the basin. By about 2000 years ago the lake had evolved from a shallow, saline, and alkaline pool to its present depth and extent.